Exploring physical activity behavior in middle-aged Taiwanese women based on the theory of planned behavior. (9th August 2022) - Chou, Hsueh-Fen; Weng, Li-Chueh; Wang, Yafen
ABSTRACT: The study aimed to apply the theory of planned behavior (TPB) to understand middle-aged women's behavior of physical activity (PA). We recruited 185 women between 45 and 64 years (mean: 53.2 ± 5.6) for this cross-sectional study. Participants complete demographic data and an exercise behavior questionnaire including attitudes, subjective norms, perceived behavioral control (PBC), and intention. Means, frequencies, and t -tests were used. To test TPB, we used structural equation modeling. Fit indices for this model demonstrate a good fit: chi-square and degree of freedom ratio X 2 /df = 2.14 ( p  = .34), goodness of fit =.97, comparative fit index =.99, root mean square error of approximation =.019, and Akaike information criterion = 28.14. Significant positive correlations between subjective norms and intention (ß=.18, p  < .05) and between PBC and intention (ß=.48, p  < .01). Women believed that close family and friends promoted their intention to perform PA. Increased PBC would positively enhance their intention. Findings showed that PBC was the strongest predictor. Enhancing women's PBC over their PA can improve their intention. Future researchers are encouraged to examine the barriers to and benefits of improving PBC so that a useful and effective intervention can be designed to promote PA.